Diet, psychosocial stress, and Alzheimer's disease–related neuroanatomy in female nonhuman primates. Issue 5 (3rd December 2020) - Frye, Brett M.; Craft, Suzanne; Register, Thomas C.; Andrews, Rachel N.; Appt, Susan E.; Vitolins, Mara Z.; Uberseder, Beth; Silverstein‐Metzler, Marnie G.; Chen, Haiying; Whitlow, Christopher T.; Kim, Jeongchul; Barcus, Richard A.; et al.
Abstract: Introduction: Associations between diet, psychosocial stress, and neurodegenerative disease, including Alzheimer's disease (AD), have been reported, but causal relationships are difficult to determine in human studies. Methods: We used structural magnetic resonance imaging in a well‐validated non‐human primate model of AD‐like neuropathology to examine the longitudinal effects of diet (Mediterranean vs Western) and social subordination stress on brain anatomy, including global volumes, cortical thicknesses and volumes, and 20 individual regions of interest (ROIs). Results: Western diet resulted in greater cortical thicknesses, total brain volumes, and gray matter, and diminished cerebrospinal fluid and white matter volumes. Socially stressed subordinates had smaller whole brain volumes but larger ROIs relevant to AD than dominants. Discussion: The observation of increased size of AD‐related brain areas is consistent with similar reports of mid‐life volume increases predicting increased AD risk later in life. While the biological mechanisms underlying the findings require future investigation, these observations suggest that Western diet and psychosocial stress instigate pathologic changes that increase risk of AD‐associated neuropathology, whereas the Mediterranean diet may protect the brain.